Reaching at-Risk Student Populations During a Pandemic: The Impacts of Covid-19 on Prison Education - Montenegro, Desiree Ann (Frontiers in Communication, 2021)
Since the onset of the COVID-19 pandemic, higher education programs in prisons have suffered due to continued overcrowding, modified schedules, limited access to facilities, 21,183 documented COVID-19 positive cases in the US Correctional Facilities, an over 11 million documented COVID-19 positive cases in Correctional Facilities across the globe and seemingly uncontrollable outbreaks. Existing challenges for prison education programs have been substantially exacerbated by the COVID-19 pandemic, emphasizing a need to reinvigorate correspondence instruction modalities of teaching so that effective instruction in prison systems can continue. This study analyzes the current situation, strengths, weakness and opportunities available for best communication practices within the established instructional modality in prison and correspondence education during the current pandemic.